Essential requirement for major histocompatibility complex recognition in T-cell tolerance induction. - Lamb, JR; Feldmann, M (1984)
The induction of T-cell responses involves the recognition of extrinsic antigen in association with antigens of the major histocompatibility complex (MHC), in mice and man, with different T cells recognizing antigen in association with either class I (H-2K/D, HLA-A, B, C) or class II (Ia, HLA-D/DR) MHC antigens. However, the requirement of MHC recognition in the induction of immunological tolerance remains ill defined. With human T helper clones recognizing synthetic peptides of influenza haemagglutinin (HA-1), we have investigated the nature of antigen-induced stimulation, and antigen-induced antigen-specific unresponsiveness, immunological tolerance. Tolerance is not due to cell death, as the cells remain responsive to interleukin-2 and is associated with the loss of T3 antigen from the cell surface. Using monoclonal antibodies to the non-polymorphic regions of human class II antigens to inhibit the induction of T-cell tolerance we report here that induction of tolerance requires the recognition of MHC antigens.